REFLECTION OF NATIONAL MENTALITY AND STEREOTYPES IN JOKES - Rustamov Ilkhom Tursunovich (Sciental Journals Publishing, 2025)
This article examines the reflection of national mentality and stereotypes in jokes. Jokes are analyzed as an important linguocultural phenomenon expressing national culture and value systems. The article provides a comparative analysis of linguistic expressions of national character, cultural identity, and stereotypes in Uzbek and English jokes. Additionally, the issue of developing communicative competence through stereotypes reflected in jokes within language teaching processes is also explored. According to research results, jokes are identified not only as symbols of folk humor but also as communicative tools that express national mentality and play an important role in intercultural relations.